2011
DOI: 10.9753/icce.v32.management.18
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Storm Surge Disasters in Asia

Abstract: Field surveys were performed in the southwest of Bangladesh after cyclone Sidr in 2007 and in Yangon River Basin after Cyclone Nargis in Myanmar in 2008 in order to learn lessons out of severe disasters due to storm surges. Spatial distributions of inundation heights were measured around the most damaged areas. Both Bangladesh and Myanmar were severely damaged, but the preparedness against storm surge and the experiences were different. The resultant total losses in these two countries were significantly diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…Shibayama et al (2014) indicated these rapid changes in water levels were associated with sudden changes in wind direction and can cause tsunami-like hydraulic bore in the large front of the storm surge, as observed by coastal residents. This type of bore structure was also observed by local people for the case of the storm surge associated with cyclone SIDR in 2007 (Shibayama et al 2009;Shibayama 2010). Figure 14 shows the route of the model typhoon under different global warming scenarios.…”
Section: Boundary Conditions Under Global Warming Scenariosmentioning
confidence: 75%
“…Shibayama et al (2014) indicated these rapid changes in water levels were associated with sudden changes in wind direction and can cause tsunami-like hydraulic bore in the large front of the storm surge, as observed by coastal residents. This type of bore structure was also observed by local people for the case of the storm surge associated with cyclone SIDR in 2007 (Shibayama et al 2009;Shibayama 2010). Figure 14 shows the route of the model typhoon under different global warming scenarios.…”
Section: Boundary Conditions Under Global Warming Scenariosmentioning
confidence: 75%